Spatial Compounding of 3-D Fetal Brain Ultrasound Using Probabilistic Maps - Perez-Gonzalez, Jorge; Arambula-Cosio, Fernando; Guzman, Mario; Camargo, Lisbeth; Gutierrez, Benjamin; Mateus, Diana; Navab, Nassir; Medina-Banuelos, Veronica (Ultrasound in Medicine and Biology, 2018)
A new method to address the problem of shadowing in fetal brain ultrasound volumes is presented. The proposed approach is based on the spatial composition of multiple 3-D fetal head projections using the weighted Euclidean norm as an operator. A support vector machine, which is trained with optimal textural features, was used to assign weighting according to the posterior probabilities of brain tissue and shadows. Both phantom and real fetal head ultrasound volumes were compounded using previously reported operators and compared with the proposed composition method to validate it. The quantitative evaluations revealed increases in signal-to-noise ratio ≤35% and in contrast-to-noise ratio ≤135% using real data. Qualitative comparisons made by obstetricians indicated that this novel method adequately recovers brain tissue and improves the visibility of the main cerebral structures. This may prove useful both for fetal monitoring and in the diagnosis of brain defects. Overall this new approach outperforms spatial composition methods previously reported.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Fetal brain; Image fusion; Spatial composition; Speckle reduction; Support vector machine; Ultrasound shadows